Gender, planning, and academic expectations in first-year higher education students: testing two alternative mediation models - Sonia Alfonso; António M. Diniz; Manuel Deaño; Fernando Tellado; Mar García-Señorán; Ángeles Conde; Valentín Iglesias-Sarmiento (Psicologia: Reflexão e Crítica, 2020)
Abstract We examined the relationships among gender, planning, and academic expectations through the testing of two alternative models with latent variables tested with LISREL 8.80: one model considered planning as a mediator of the relationship between gender and academic expectations, and the other model considered academic expectations as mediators of the relationship between gender and planning. Participants were 662 first-year higher-education students from two academic years, predominantly female (60%) and mainly with majors in the juridical-social field (66.2%). The Inventario sobre Estrategias Metacognitivas (IEM; Inventory of Metacognitive Strategies) and the Academic Perceptions Questionnaire (APQ) were applied at the beginning of the first semester to assess planning and academic expectations, respectively. Multigroup confirmatory factor analysis was used to test the IEM’s structure after examining its psychometric properties with the sample from the first academic year (N = 338). The test of the alternative mediation models with the full sample indicates that the best model was that with planning as a mediator. In this model, gender directly predicted only two APQ academic expectations, but with the mediation of planning, gender predicted all seven academic expectations. Women showed higher levels of academic expectations and planning than did men. The results are discussed at both the theoretical and practical levels.